Efektivitas Konseling Kelompok dalam Meningkatkan Kesejahteraan Mental - Alisya I’tiqafah; Sri Rahayu; Nayma Alia Putri; Aisyah Rahmaliza; Ratna Sari Dewi (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of the times is growing day by day. Not only focusing on technological developments, but intelligence and also the thoughts of each individual also continue to develop with the times. However, not only that, but mental health is also getting more attention with the times. Not only adults can experience mental health disorders, but this also happens to children and adolescents. This study aims to see the effect and also to understand how the effectiveness of group counseling in improving mental well-being, so that more people can get the support they need. This research uses the literature method, by taking data from journals that have discussed this topic before. The result of this research is that group counseling can improve individuals' mental health, especially for those who are not experiencing severe emotional disturbances. The process relies on the relationship between the leader and group members which involves acceptance, trust, and a sense of security.